2010
DOI: 10.1185/03007995.2010.536208
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab in the management of oral corticosteroid-dependent IGE-mediated asthma patients

Abstract: In our series, a substantial, safe decrease in oral corticosteroid requirements was observed due, at least to some extent, to omalizumab therapy. Oral corticosteroids were withdrawn in three-quarters of the patients. We were unable to identify a factor able to predict which patients would benefit most from omalizumab treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 14 publications
1
22
0
2
Order By: Relevance
“…A meta-analysis of 7 studies showed that omalizumab significantly reduced the number of asthma exacerbations and emergency room visits by 38% and 47%, respectively, in severe persistent asthmatics (55). Domingo et al recently showed that it could even have some corticosteroid sparing effect in this group of individuals (56). These results however have not been validated with large randomized trials.…”
Section: Current and Emerging Concepts In Management Of Steroid Resismentioning
confidence: 94%
See 1 more Smart Citation
“…A meta-analysis of 7 studies showed that omalizumab significantly reduced the number of asthma exacerbations and emergency room visits by 38% and 47%, respectively, in severe persistent asthmatics (55). Domingo et al recently showed that it could even have some corticosteroid sparing effect in this group of individuals (56). These results however have not been validated with large randomized trials.…”
Section: Current and Emerging Concepts In Management Of Steroid Resismentioning
confidence: 94%
“…Cyclosporine(52) Gold(52) Methotrexate(53,54) Anti-Ig E: Omalizumab, reduces frequency of asthma exacerbations and emergency room visits(55,56) Cytokines and Cytokine inhibitors: Modulation of cytokines playing an important role in SRA and inflammation. TNF Alpha(57,58) Interferon (60) Mutated Anti-IL-4 blocking IL-4R subunit (Pitrakinra)(63) Anti-IL-5 (mepolizumab)(61,62) Anti-IL-9(57) Anti-IL-13 (lebrikizumab)(65) Intravenous immunoglobulin: Reduces steroid requirements but does not improve lung function(59) Chemokine receptor antagonists:(21,66) CXCR1/2 directed against neutrophils CCR3 directed against eosinophils CRTH2 directed against eosinophils and Th2 cells Miscellaneous:(21,67) MAPK inhibitors AP-1 inhibitors NF-κB inhibitors IL-10 secreting T regulatory cell inducers --------------------------------------------------------------------------------------------------------------------------------TNF: Tumor necrosis factor; IL: Interleukin; AP-1: Activated protein-1; NF--B: Nuclear factor-B; MAPK: Mitogen activated protein kinases Lung biopsy showing features of asthma: mucous stasis, goblet cell hyperplasia, basement membrane thickening, and smooth muscle hypertrophy with eosinophilic infiltrates and hemosiderin laden macrophages (H and E stain, 10x, 25x and 100x magnification) 28 Venn diagram showing various subsets of Asthma.…”
mentioning
confidence: 99%
“…However, the capacity of this drug to exert a significant steroid-sparing effect has been tested in several studies but remains to be established, given that omalizumab was studied mainly as add-on therapy in moderate and severe asthma patients not routinely receiving oral corticosteroids. In a recent uncontrolled clinical study of corticosteroid-dependent severe asthma, a substantial safe decrease in oral corticosteroid requirements was observed resulting to at least some extent from omalizumab therapy [35].…”
Section: Omalizumab Studiesmentioning
confidence: 99%
“…Recent expert panel guidelines now also recommend omalizumab in step V patients with severe allergic asthma and increased levels of IgE either as an alternative or in addition to oral corticosteroids [24]. However, there is little evidence about the ability of omalizumab to have significant steroid sparing effect, with the exception of a recent uncontrolled clinical trial in which a substantial dose reduction in oral corticosteroid requirements was shown [25].…”
Section: Anti-ige Tacticsmentioning
confidence: 99%